El ambiente escolar y el proceso de enseñanza-aprendizaje en las niñas y niños del primer grado de educación general básica de la unidad educativa Manuel José Rodríguez de la parroquia Malacatos, período 2013 – 2014. Lineamientos alternativos - Soto Galvez, Andrea Maribel (2015)
The present research: THE SCHOOL ENVIRONMENT AND THE TEACHING-LEARNING PROCESS OF THE CHILDREN FROM FIRST GRADE OF THE GENERAL BASIC EDUCATION IN THE EDUCATIONAL UNIT “MANUEL JOSÉ RODRÍGUEZ” FROM MALACATOS PARISH, 2013 – 2014. ALTERNATIVE GUIDELINES. This research has the general objective: To determine the relationship of the school environment with the teaching-learning process of the children from the first grade of the General Basic Education in the educational Unit “Manuel José Rodríguez” from Malacatos Parish, 2013-2014. The research development was supported by the following methods: analytic, synthetic, inductive and deductive, the same that were used for processing the empirical information as well as case analysis, making comparisons, relationships and generalizations to determine and understand the causes problems or difficulties in the relationship of the school environment with the process of teaching-learning of children. The technique used in the research was the survey; it was designed and validated with closed-ended questions and was applied individually to three teachers and twenty-five parents; and an observation guide that was made to the school environment where twenty-five children are. The instrument applied individually to teachers and parents is equivalent to 100% know that the school environment is related to the teaching-learning process and the observation made to the school environment where children corresponding to 100% developed, environmental factors that lack of management by institutional authorities no improvement in the classroom environment characterized. In conclusion it has been determined that the existing environmental factors such as: the lack of lighting and ventilation, weather conditions, limited physical space and environmental stressors is related to the learning that children show, because they do not have a favorable environment to overcome the limitations that currently have in the teaching-learning process. Therefore, it is recommended to implement and execute the renewal and adaptation of the facilities of the school, in order to improve the school environment and overcome the difficulties in teaching and learning-processes.